Neoadjuvant Therapy in Operable Breast Cancer: Application to Triple Negative Breast Cancer. (1st August 2013) - Ademuyiwa, Foluso O.; Ellis, Matthew J.; Ma, Cynthia X.
Abstract : Systemic treatment for triple negative breast cancer (TNBC: negative for the expression of estrogen receptor and progesterone receptor and HER2 amplification) has been limited to chemotherapy options. Neoadjuvant chemotherapy induces tumor shrinkage and improves the surgical outcomes of patients with locally advanced disease and also identifies those at high risk of disease relapse despite today's standard of care. By using pathologic complete response as a surrogate endpoint, novel treatment strategies can be efficiently assessed. Tissue analysis in the neoadjuvant setting is also an important research tool for the identification of chemotherapy resistance mechanisms and new therapeutic targets. In this paper, we review data on completed and ongoing neoadjuvant clinical trials in patients with TNBC and discuss treatment controversies that face clinicians and researchers when neoadjuvant chemotherapy is employed.